IMPLEMENTASI FUNGSI PENGAWASAN DEWAN PERWAKILAN RAKYAT DAERAH DALAM PENGGUNAAN ANGGARAN PEMBANGUNAN INFRASTRUKTUR DI KECAMATAN MALINAU KOTA KABUPATEN MALINAU - Syafitri Syafitri; Adri Patton; Djumadi Djumadi (Jurnal Paradigma (JP), 2019)
The purpose of this study is to describe and analyze the Implementation of the Supervisory Function of the Regional House of Representatives in the budget’s utilizatin of Infrastructure Development in Sub-district Malinau Kota. Types of research conducted include descriptive qualitative. The data source is taken by informant and key informance chosen purposively and direct observation result, and supported by secondary data. The data analysis used is an interactive model. The result of the research shows that the implementation of oversight function by DPRD of Malinau District towards Infrastructure Development in Sub-district Malinau Kota has complied with the prevailing regulations, but DPRD supervision is not maximal yet. Keywords: Implementation, DPRD, Oversight Function